FAKTOR-FAKTOR YANG MEMPENGARUHI CAPAIAN KOTA AMBON SEBAGAI KOTA KREATIF BIDANG MUSIK - Umarella, Fathur Rahman; Roychansyah, M. Sani (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2026)
Ambon, as a member of the UNESCO Creative Cities Network (UCCN) in the field of music, has demonstrated a strong commitment to leveraging local potential to support creativity-based development. This achievement is significant and warrants an examination of the factors influencing its success to ensure its sustainability. This study aims to describe the factors influencing Ambon’s achievement as a Creative City of Music. The research employs a descriptive qualitative approach, involving data collection through document studies, observations, and interviews with stakeholders in Ambon. The results indicate that there are two main factors influencing Ambon’s achievement: internal and external factors. Internally, government commitment—reflected in policy support and budgeting—shows a moderate level of influence, while collaboration among stakeholders is categorized as strong. Externally, the influencing factors include commitment and collaboration. The implementation of national creative city policies demonstrates a strong influence, supported by significant local government policies. However, budget support through funding assistance from Badan Ekonomi Kreatif (Bekraf) and the Maluku Provincial Government is inconsistent, resulting in a moderate level of influence. On the other hand, collaboration between Ambon Music Office (AMO) and various stakeholders, including Bekraf and Indonesian Creative Cities Network (ICCN), shows a strong influence, with sustained partnerships that continue to support Ambon as a Creative City in the field of music.